The effects of PPAR-γ inhibition on gene expression and the progression of induced osteogenic differentiation of human mesenchymal stem cells. (19th May 2014) - Granéli, Cecilia; Karlsson, Camilla; Brisby, Helena; Lindahl, Anders; Thomsen, Peter
Abstract: Mesenchymal stem cells (MSCs) can differentiate into several cell types, such as osteoblasts and adipocytes, both in vitro and in vivo . Although these two differentiation pathways are distinct from each other, cross-communication between cells of the two lineages exists both systemically and peripherally in the tissue. The transcription factor PPAR-γ, the main switch in adipogenic differentiation of MSCs, has previously been described to have a negative effect on osteogenic differentiation. The aim of this study was to investigate the effect of PPAR-γ inhibition on osteogenic differentiation of human MSCs, in vitro . Extracellular matrix analysis and quantification of osteogenic markers, revealed how these cells respond when the adipogenic differentiation pathway is blocked during induction of osteogenic differentiation. The inhibition leads to a significant increase in mineralization of the extracellular matrix, as well as an increased activity or up-regulated gene expression of alkaline phosphatase, the key enzyme involved in matrix mineralization. Furthermore, it was also demonstrated by microarray analysis, that PPAR-γ inhibition during osteogenic induction leads to a significant up-regulation of a number of genes related to both osteogenesis and adipogenesis such as c10orf10, leptin, GDF5 and KLF15. In conclusion, inhibition of PPAR-γ during induction of osteogenesis leads to increased osteogenic differentiation of human MSCs.